How specialized are writing-specific brain regions? An fMRI study of writing, drawing and oral spelling. (March 2017) - Planton, Samuel; Longcamp, Marieke; Péran, Patrice; Démonet, Jean-François; Jucla, Mélanie
Abstract: Several brain imaging studies identified brain regions that are consistently involved in writing tasks; the left premotor and superior parietal cortices have been associated with the peripheral components of writing performance as opposed to other regions that support the central, orthographic components. Based on a meta-analysis by Planton, Jucla, Roux, and Demonet (2013), we focused on five such writing areas and questioned the task-specificity and hemispheric lateralization profile of the brain response in an functional magnetic resonance imaging (fMRI) experiment where 16 right-handed participants wrote down, spelled out orally object names, and drew shapes from object pictures. All writing-related areas were activated by drawing, and some of them by oral spelling, thus questioning their specialization for written production. The graphemic/motor frontal area (GMFA), a subpart of the superior premotor cortex close to Exner's area (Roux et al., 2009), was the only area with a writing-specific lateralization profile, that is, clear left lateralization during handwriting, and bilateral activity during drawing. Furthermore, the relative lateralization and levels of activation in the superior parietal cortex, ventral premotor cortex, ventral occipitotemporal cortex and right cerebellum across the three tasks brought out new evidence regarding their respective contributions to the writing processes.